Developing real‐world evidence from real‐world data: Transforming raw data into analytical datasets. Issue 1 (14th October 2021) - Bastarache, Lisa; Brown, Jeffrey S.; Cimino, James J.; Dorr, David A.; Embi, Peter J.; Payne, Philip R.O.; Wilcox, Adam B.; Weiner, Mark G.
Abstract: Development of evidence‐based practice requires practice‐based evidence, which can be acquired through analysis of real‐world data from electronic health records (EHRs). The EHR contains volumes of information about patients—physical measurements, diagnoses, exposures, and markers of health behavior—that can be used to create algorithms for risk stratification or to gain insight into associations between exposures, interventions, and outcomes. But to transform real‐world data into reliable real‐world evidence, one must not only choose the correct analytical methods but also have an understanding of the quality, detail, provenance, and organization of the underlying source data and address the differences in these characteristics across sites when conducting analyses that span institutions. This manuscript explores the idiosyncrasies inherent in the capture, formatting, and standardization of EHR data and discusses the clinical domain and informatics competencies required to transform the raw clinical, real‐world data into high‐quality, fit‐for‐purpose analytical data sets used to generate real‐world evidence.